Effectiveness of training, what are the dimensions involved. Case study in Pusat Pembelajaran Bank Simpanan Nasional / Khairiyah Kamal - Kamal, Khairiyah (Faculty of Business and Management, 2010)
In this project paper, the aim of this research is to study what are the dimensions involved to the effectiveness of training program in Pusat Pembelajaran Bank Simpanan Nasional (PPBSN). This study involved staffs of Bank Simpanan Nasional who attended training program in Pusat Pembelajaran Bank Simpanan Nasional (PPBSN). This research only focused those were involved in Customer Service and Change Mind Set Training program in September and October as a respondent. Four factors have been used to determine the effectiveness of training program in PPBSN which were the quality of trainers, organizational support, strategic training program and employee‟s selfefficacy.